Implementasi CRM dalam Meningkatkan Kualitas Layanan pada PT PLN Icon Plus SBU Jawa Bagian Timur dengan Memanfaatkan Sistem Teknologi Informasi - Rosida, Fira; Rusdianto, R. Yuniardi (Ikatan Da'i Indonesia, 2025)
The purpose of this study is to examine how PT PLN Icon Plus SBU Jawa Bagian Timur uses information technology systems to improve service quality through the use of customer relationship management (CRM). Effective customer relationship management is now more crucial than ever in the digital age to guarantee client loyalty and happiness. As a provider of information and communication technology services, PT PLN Icon Plus SBU Jawa Bagian Timur has put in place a technology-based CRM strategy to improve customer interactions, handle data effectively, and boost service responsiveness. This study contributes by highlighting the critical role that information technology plays in helping CRM enhance service quality in the telecom and energy industries and by offering tactical suggestions for future advancement.